Fostering entrepreneurial spirit: Elevating attitudes through local wisdom-infused project-based learning - Imam Hanafi; M. Marzuki; Nur Khikmah; Indro Nugroho (Research and Development in Education (RaDEn), 2024)
Students often complete assignments just to fulfill their obligations, so project-based learning with an entrepreneurial orientation is expected to produce products with more market value. The purpose of this study was to improve students' entrepreneurial attitudes after implementing project-based learning on ecology material. This quasi-experimental study used a pretest-posttest control group design. A total of 48 students selected through purposive sampling technique were divided into experimental and control groups. The data collection instruments used were concept mastery tests, questionnaires, observations, and documentation while data analysis used descriptive analysis and mean difference tests. The results of the analysis showed that there was an increase in students' local wisdom-based entrepreneurial attitudes through the application of project-based learning models on Ecology material. Therefore, educators and curriculum developers adopt an approach that not only improves academic outcomes but also fosters entrepreneurial skills that are important for students' future success.